The Social Cost of Growth and Energy Use in Newly Industrialized Countries: The Role of CO₂ Emissions and Renewable Transitions - Wijayanti, Diah Lufti; Sasana, Hadi; Hidayah, Atika; Prasetyanto, Panji Kusuma (International Journal of Energy Economics and Policy, 2025)
This study aims to analyze the factors influencing government spending in the health sector in ten newly industrialized countries. Focusing on economic, social, energy, and environmental aspects, this study aims to determine how variables such as economic growth, urbanization, fossil and renewable energy consumption, and carbon dioxide (CO₂) emissions contribute to the social costs of health. The methodology used is panel data analysis with multiple regression, using secondary data obtained from international institutions such as the World Bank and the IEA, processed using Stata 17 software. The results show that economic growth and urbanization significantly increase government spending in the health sector, while fossil and renewable energy consumption negatively affect the social costs of health. In addition, CO₂ emissions and coal consumption do not show a significant effect, emphasizing the importance of sustainable energy management. Based on these findings, recommended policies include increasing investment in renewable energy and environmentally friendly technologies, managing sustainable urbanization, and establishing energy policies that support efficiency and emission reduction. This step is expected to reduce social costs in the health sector while maintaining environmental sustainability, supporting the achievement of the Sustainable Development Goals (SDGs) and improving the quality of life of people in developing countries.